2017
DOI: 10.1007/s10953-017-0679-7
|View full text |Cite
|
Sign up to set email alerts
|

Barium and Radium Complexation with Ethylenediaminetetraacetic Acid in Aqueous Alkaline Sodium Chloride Media

Abstract: The speciation of Ra 2? and Ba 2? with EDTA was investigated at 25°C in aqueous alkaline NaCl media as a function of ionic strength (0.2-2.5 molÁL -1 ) in two pH regions where the EDTA 4-and HEDTA 3-species dominate. The stability constants for the formation of the [BaEDTA] 2-and [RaEDTA] 2-complexes were determined using an ion exchange method. Barium-133 and radium-226 were used as radiotracers and their concentrations in the aqueous phase were measured using liquid scintillation counting and gamma spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The coordination geometry relies on a monocapped tetragonal prism and is completed by water molecules [122]. The coordination chemistry of radium is little explored as it is radioactive, yet seems to be similar to the one of barium [123].…”
Section: Bariummentioning
confidence: 99%
“…The coordination geometry relies on a monocapped tetragonal prism and is completed by water molecules [122]. The coordination chemistry of radium is little explored as it is radioactive, yet seems to be similar to the one of barium [123].…”
Section: Bariummentioning
confidence: 99%
“…23 Previous efforts to investigate the aqueous coordination chemistry of Ra 2+ have focused on linear polyaminocarboxylate ligands, such as ethylenediamine(tetraacetic) acid (EDTA). [24][25][26][27][28] These studies, which employed either long-lived 226 Ra or tracer 228 Ra, demonstrate that complexes of Ra 2+ with these ligands form, albeit with lower stability constants than the lighter alkaline earth ions. Competition extraction studies have also shown that macrocycles such as DOTA and Kryptox 2.2.2 can bind to 223 Ra, although the biological stability of these complexes has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…These values can provide valuable insight into the fundamental coordination preferences of Ra 2+ and serve as a useful metric to compare binding strengths and selectivities among chelators. To date, stability constant studies of Ra 2+ complexes have been limited to simple organic acids and acyclic polyaminocarboxylate ligands, 6,10 which are known to form complexes of low stability in vivo with many radiometals. 7 a Here, we expand our knowledge of the stability constants of Ra 2+ complexes to include two chelators that are directly relevant for use in biomedical applications.…”
mentioning
confidence: 99%